Rabbit dental disease and calcium metabolism – the science behind divided opinions. (22nd August 2013) - Jekl, V.; Redrobe, S.
<x xml:space="preserve">Abstract</x> Dental disease is considered as one of the, if not, the most common disorders seen in pet rabbits. This article provides a review of the scientific literature and an overview of the peculiarities of calcium homeostasis in the rabbit in an attempt to draw together current thinking on the cause of dental disease. A complete understanding of the aetiology and pathophysiology of rabbit dental disease is necessary for the veterinary practitioner to establish a proper therapeutic plan, prognosis and ultimately prevention of this common cause of morbidity and mortality in pet rabbits.